PRODUKSI KAMUS KANHAN500 - Nugroho, Rukmono Danang; Kuncoro, Ogi Yoga Abi; Fernadita, Atmi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Indonesian Kanji dictionaries that were found in the bookstore during this sequence only present way of writing and examples of using the Kanji letters. We have not found a dictionary that describes how to learn kanji effectively as a way to remember kanji. In addition, examples of using Kanji letters did not focus on vocabulary learning based on the level of the level of Japanese language learning, vocabulary should be memorized beforehand was also not included. Until now there are so many Indonesian Japanese language learners who have difficulties in learning kanji. Actually, studying Japanese kanji means we will be able to guess the vocabulary of the Korean language because a lot of similarities between Japanese and Korean vocabulary. Thus, the need for kanji dictionary compiled not only present how to write Kanji and examples of using Kanji letters but also how to remember the kanji, and division level based vocabulary. Therefore, we try to make the dictionary and have purpose of: 1 Provides media that can facilitate learners understand and remember Japanese kanji. 2 Provide instructional media can also enrich the science of Japanese language learners with vocabulary presented Sino Korea, making it easier to learn Korean vocabulary. 3 Adding references and resources kanji that have not featured in publications kanji dictionaries Indonesia. Method that was used to make this dictionary is a method of learning kanji by drawing the kanji origins and reminders words. The words made a principled reminder on the origins of Kanji is Shoukei Moji, Shiji Moji, Kai-I Moji, and Keisei moji. However, these reminders words also made based on our creativity to make it easier to remember the kanji learners. Thus, studying kanji in this way will definitely make kanji learners easily remember the form of starch.Keywords: dictionary, kanji, hanja.